2009
DOI: 10.1038/mt.2009.90
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 27 as a New Therapeutic Target for Radiation Sensitization of Head and Neck Squamous Cell Carcinoma

Abstract: In a wide range of human cancers, increased levels of heat shock protein 27 (Hsp27) are closely associated with tumorigenesis, metastasis, resistance to anticancer therapeutics, and thus poor prognosis. In this study, we evaluate the radiosensitizing effects of Hsp27 gene silencing using OGX-427, a second-generation antisense oligonucleotide (ASO), on the radioresistant head and neck squamous cell carcinoma (HNSCC) SQ20B cells. In vitro, the downregulation of Hsp27 significantly enhanced radiation-induced apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 41 publications
0
50
0
Order By: Relevance
“…Photomicrographs of tumor sections and quantification of Ki67 marker revealed that the lack of tumor development with PA11 and 50 was due to an alteration of proliferation process (Figures 6a and b). We have previously reported that a Hsp27 RNAi induces a small delay in tumor progression, without modulation of the Ki67 marker (Hadchity et al, 2009). Moreover, TUNEL assay on tumor section showed that PA11 and PA50 did not increase apoptosis, probably as a result of a lack of pro-apoptotic stimulation (Figure 6a).…”
Section: Aptamers Inhibit the Proliferation Of Tumor Xenograftsmentioning
confidence: 95%
See 3 more Smart Citations
“…Photomicrographs of tumor sections and quantification of Ki67 marker revealed that the lack of tumor development with PA11 and 50 was due to an alteration of proliferation process (Figures 6a and b). We have previously reported that a Hsp27 RNAi induces a small delay in tumor progression, without modulation of the Ki67 marker (Hadchity et al, 2009). Moreover, TUNEL assay on tumor section showed that PA11 and PA50 did not increase apoptosis, probably as a result of a lack of pro-apoptotic stimulation (Figure 6a).…”
Section: Aptamers Inhibit the Proliferation Of Tumor Xenograftsmentioning
confidence: 95%
“…]) (Equation (1)), where SF is survival fraction and D represents radiation doses (Hadchity et al, 2009). The SF at 2 Gy (SF2) was determined as an index of radiosensitivity.…”
Section: Gel Electrophoresis and Immunoblottingmentioning
confidence: 99%
See 2 more Smart Citations
“…Antisense oligonucleotides (ASOs) are powerful tools to inhibit target gene expression in a sequence-specific manner. Thus, OGX-427 (Oncogenex), a second-generation ASO drug that in preclinical experiments significantly decreased the levels of Hsp27 and induced apoptosis, acted as a chemosensitizer in combination with gemcitabine (Baylot et al 2011) and as a radiation sensitizer in patients with radioresistant head and neck squamous cell carcinomas (Hadchity et al 2009). Phase I and II clinical trials on patients with bladder and prostate cancers that Fig.…”
Section: Discussionmentioning
confidence: 99%